How I Grow: Months Five and Six - Millie Ferrer; Keith Gouin; Anne M. Fugate (EDIS)
Welcome to another fascinating stage in your baby’s development. At this age, babies are very happy and sociable, and much more physically active. You will see your baby’s interest in his surroundings grow. Your baby will respond more to people and objects. What a great time to be a parent! Your baby is developing a strong curiosity about the world around him. Parents who lovingly attend to their baby’s needs help him develop physically, socially, emotionally, and intellectually. This document is FCS2219, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, University of Florida, UF/IFAS, Gainesville, FL 32611. First published: August 2003.